Construction productivity and global inequality - Saumik Paul; Kunal Sen (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2023)
Two well established stylized facts of economic development are a strong correlation between investment and income, and large differences in investment rates across countries. Construction is the largest component of investment. This paper examines the implications of heterogeneity in construction productivity on cross-country income disparity. We estimate the 10:1 spread in construction productivity among 145 countries in 2005 as a factor of 61.7-fold. Based on a general equilibrium model with input-output linkages, we find that the 10:1 spread in income per capita declines by 45 per cent when the construction productivity gap is eliminated. Sectoral characterization of the aggregate effect of a change in construction productivity shows heterogeneous sectoral contributions to income convergence. Electrical equipment, metals, and transport equipment play stronger roles in transforming the effect of a change in construction productivity to the aggregate level in China compared with other countries.
Keywords: O4; O11; E01; L74; 330; productivity; construction; input– output linkages; income inequality